ChemInform Abstract: 2‐Substituted Thiazole‐4‐carboxamide Derivatives as Tiazofurin Mimics: Synthesis and in vitro Antitumor Activity. Issue 32 (24th July 2014) - Popsavin, Mirjana; Kojic, Vesna; Spaic, Sasa; Svircev, Milos; Bogdanovic, Gordana; Jakimov, Dimitar; Aleksic, Lidija; Popsavin, Velimir
Abstract: Title compounds (I) ‐ (III) are prepared by multistep sequences starting from D‐xylose or D‐arabinose, respectively.